The radical anion and dianion of tetraazapentacene - Ji, Lei; Biegger, Philipp; Geyer, Florian Ludwig; Tverskoy, Olena; Schaffroth, Manuel; Han, Jie; Dreuw, Andreas; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2016)
The mono- and bis-reduction of 6,13-bis((triisopropylsilyl)ethynyl)quinoxalino[2,3-b]phenazine (1) with potassium anthracenide in THF is reported. Both the radical anion 1.− and the dianion 12− were isolated and characterized by optical and structural (single-crystal X-ray diffraction) methods. Solutions of the radical anion 1.− were stable in air for several hours and characterized by EPR spectroscopy. Dianion 12− is highly fluorescent and photostable.